Application of a Mix of Vegetables Residues as Inhibitor for Carbon Steel - Barreto,L.S. (2022)
This work investigates the synergistic use of Theobroma cacao (Cocoa), and Elaeis guineensis (Palm oil) as corrosion inhibitors for carbon steel in 0.5 mol.L-1 hydrochloric acid solution, in the absence and presence of different mixture concentrations of the studied compounds. The efficiency of corrosion inhibitors was studied by gravimetric tests and the corrosion resistance by electrochemical tests, such as electrochemical impedance spectroscopy (EIS) and polarization curves. The chemical composition of the cocoa bark powder and palm kernel cake powder was evaluated by Fourier transform infrared spectroscopy (FTIR). The results of the gravimetric tests showed an inhibition efficiency of 79% for the cocoa bark powder and 76% for palm kernel cake powder, however, the mixture of the compounds presented an inhibition superior to 94%, showing the great synergism between the studied species. These results corroborate the values obtained from EIS.